2022
DOI: 10.1186/s12891-022-05959-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between adherence to a home exercise program and central sensitization, pain intensity, and functionality in individuals with knee osteoarthritis

Abstract: Objective To analyze the association between adherence to a home exercise program and central sensitization, pain intensity, and functionality in individuals with knee osteoarthritis (KOA). Methods A cross-sectional study was conducted involving 57 individuals with KOA. Evaluations were performed using the Exercise Adherence Rating Scale (EARS), the numerical rating scale (NRPS), the International Knee Documentation Committee (IKDC), The Central Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…For patients suffering from long-term OA, pain may become a source of exercise phobia, and muscle strength may directly or indirectly influence their physical activities [ 45 ]. Studies have found no significant correlation between HBE and central sensitization or pain intensity, and exercise intensity does not induce more adverse reactions [ 46 48 ]. Low educational level has been identified as an important factor contributing to catastrophic pain and exercise phobia in OA patients [ 49 ], highlighting the need for healthcare providers to pay attention to psychological behavior induction and pain neuroscience education to eliminate patient fear of exercise.…”
Section: Discussionmentioning
confidence: 99%
“…For patients suffering from long-term OA, pain may become a source of exercise phobia, and muscle strength may directly or indirectly influence their physical activities [ 45 ]. Studies have found no significant correlation between HBE and central sensitization or pain intensity, and exercise intensity does not induce more adverse reactions [ 46 48 ]. Low educational level has been identified as an important factor contributing to catastrophic pain and exercise phobia in OA patients [ 49 ], highlighting the need for healthcare providers to pay attention to psychological behavior induction and pain neuroscience education to eliminate patient fear of exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Continued adherence was an interplay of multiple factors, inclusive of the perceived benefits of the exercises and the clients' selfefficacy and ability to accommodate exercises into their everyday schedules [16]. Adherence is majorly driven by the desire to wean off pharmacological pain management, avoid the need for surgery and, sustain independence in ADL without being a burden on the family [4].…”
Section: Discussionmentioning
confidence: 99%
“…Exercise therapy can be described as a therapeutic approach that relies on the consistent repetition of activities to enhance resistance and reduce the duration of impairment. Exercise has been shown to be beneficial in chronic MSK pain management due to its ability to induce adaptation of the neuromuscular system to conditions that may result in joint loading and instability during functional activities [4]. Exercise interventions can take the form of insession exercises, athome exercises, or both.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation